2020
DOI: 10.1038/s41598-020-67450-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of spin Hall magnetoresistance in heavy-metal/ferromagnetic-metal bilayers

Abstract: We present experimental data and their theoretical description on spin Hall magnetoresistance (SMR) in bilayers consisting of a heavy metal (H) coupled to in-plane magnetized ferromagnetic metal (F), and determine contributions to the magnetoresistance due to SMR and anisotropic magnetoresistance (AMR) in five different bilayer systems: W/Co 20 Fe 60 B 20 , Co 20 Fe 60 B 20 /Pt , Au/Co 20 Fe 60 B 20 , W/Co, and Co/Pt. The devices used for experiments have different interfacial properties due to either amorphou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…For Pt, i.e., for χ = HM , the charge current density reads where ρ HM is the resistivity of the Pt layer, θ SH is the spin Hall angle defined as the charge-to-spin current conversion efficiency at a very thick HM layer limit, and μ s , y HM ( z , m 1(2) ) is the spin accumulation, while for the ferromagnetic layers, i.e., χ = F 1 (χ = F 2) where ρ F 1( F 2) is the resistivity of the corresponding ferromagnetic layer, θ AMR is the AMR in the thick ferromagnetic limit (assumed for simplicity the same in both ferromagnetic layers). For more details, see, e.g., ref ( 37 ).…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…For Pt, i.e., for χ = HM , the charge current density reads where ρ HM is the resistivity of the Pt layer, θ SH is the spin Hall angle defined as the charge-to-spin current conversion efficiency at a very thick HM layer limit, and μ s , y HM ( z , m 1(2) ) is the spin accumulation, while for the ferromagnetic layers, i.e., χ = F 1 (χ = F 2) where ρ F 1( F 2) is the resistivity of the corresponding ferromagnetic layer, θ AMR is the AMR in the thick ferromagnetic limit (assumed for simplicity the same in both ferromagnetic layers). For more details, see, e.g., ref ( 37 ).…”
Section: Theorymentioning
confidence: 99%
“…Moreover, the effective fields, H DL and H FL (cf. Section 3.1 ), due to SHE and spin accumulation at the interfaces can be expressed as follows and To fit the appropriate magnetoresistance relations obtained from eq 7 , we use the following parameters: 37 , 54 56 ρ HM = 59 μΩ cm, ρ F 1( F 2) = 72.5 μΩ cm, λ HM = 1.8 nm, λ F 1 = λ F 2 = 7 nm, θ SH = 8%, θ AMR = 0.15%, β 1 = β 2 = 0.3, G s (1) = G s (2) = G r (1) = G i (1) = 10 15 Ω –1 m –2 , and G r (2) = G i (2) = 0.4 G r (1) . The parameters were also used to calculate SOT effective fields that turn out to be pivotal in the interpretation of the experimental data presented in Section 4.3 .…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The longitudinal resistance is predominately attributed to AMR arising from conducting through the metallic SRO. It is typically observed that in heavy metal/ferromagnetic metal systems contributions from AMR are significantly larger than those arising from spin Hall magnetoresistance (Karwacki et al, 2020). AMR is typically composed of two components (crystalline and non-crystalline) that have different microscopic origins.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a new MR effect has been found in heavy metal (HM)/ferromagnetic insulator (FMI) hybrid structures called the spin Hall magnetoresistance (SMR). It has been intensively studied [6][7][8][9] with additional discussions and reports on HM/ferromagnetic metal (FMM) hybrids [10][11][12]. The SMR is based on the spin Hall effect (SHE) [13][14][15][16], which occurs in the HM and converts a charge current into a perpendicular spin current.…”
Section: Introductionmentioning
confidence: 99%